Chemistry Teachers’ Perspectives on the Implementation of Interdisciplinary Science Projects in Vocational Schools: Challenges and Strategic Solutions - Lestari, Devy; Oktiani, Rosi; Lutfianasari, Ulfa; Imaduddin, Muhamad (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
The integration of interdisciplinary approaches in science education has gained increasing prominence, particularly within vocational school contexts. The research aims to identify the challenges faced by these teachers and to explore potential solutions for improving project-based instruction within the framework of Indonesia’s Merdeka Curriculum. This study investigates the perspectives of chemistry education graduates who are currently implementing interdisciplinary science projects in vocational schools across Central Java, East Java, and the Special Region of Yogyakarta. Employing a qualitative descriptive design, data were gathered from 25 purposively selected participants using an online open-ended questionnaire. Thematic analysis revealed several core challenges: limited pedagogical competence in project-based learning, difficulties in synthesizing natural and social science content, insufficient laboratory infrastructure and teaching materials, and restrictive curriculum policies that constrain instructional flexibility. These issues were especially pronounced among teachers with mono-disciplinary backgrounds in chemistry, who are now required to deliver integrated and contextualized learning. In response, the participants proposed actionable strategies, including training in contextual and project-based methodologies, mastery of interdisciplinary content, enhanced professional collaboration through musyawarah guru mata pelajaran (MGMP) / subject teacher forums, improved access to instructional resources, and flexible curriculum design. The study highlights the need for comprehensive and systemic support to enhance teachers’ capacity to deliver meaningful and vocationally relevant interdisciplinary science education. The findings provide critical insights for policymakers, curriculum developers, and teacher education institutions aiming to advance the implementation of holistic STEM education in vocational settings.